Evaluation of ribotyping as epidemiologic tool for typing Escherichia coli serogroup O157 isolates. - Martin, I E (1996)
A total of 121 representative Escherichia coli O157:H7 and O157:NM (nonmotile) isolates were characterized by ribotype, phage type, verotoxin genotype, and genomic fingerprints generated by pulsed-field gel electrophoresis. Ribotyping was not able to discriminate between O157:H7 isolates, and phage typing and pulsed-field gel electrophoresis were the most valuable and discriminatory techniques.